2009
DOI: 10.1183/09031936.00180608
|View full text |Cite
|
Sign up to set email alerts
|

Swimming pool attendance and risk of asthma and allergic symptoms in children

Abstract: Increased asthma risk has been associated with pool attendance in children but evidence is inconsistent and inconclusive. A survey was conducted of 3,223 9-12-yr-old children in Sabadell (Spain) to evaluate association between swimming pool attendance and prevalence of asthma and allergic conditions and symptoms.Parents completed a questionnaire on lifetime frequency of pool attendance and symptoms in the last 12 months (wheezing, asthma medication, rhinitis and allergic rhinitis), ever having asthma and eczem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
58
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 28 publications
9
58
1
5
Order By: Relevance
“…A Dutch study in which a semi-quantitative exposure assessment was performed also found no correlation between asthma or respiratory symptoms and average trichloramine levels in swimming pools [95]. Reported levels of trichloramine in swimming pool air from studies in Belgium [88,89], Spain [92], and the Netherlands [95] have noted overall levels that were below the 0.5 mg/m 3 recommended by the WHO [96].…”
Section: Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…A Dutch study in which a semi-quantitative exposure assessment was performed also found no correlation between asthma or respiratory symptoms and average trichloramine levels in swimming pools [95]. Reported levels of trichloramine in swimming pool air from studies in Belgium [88,89], Spain [92], and the Netherlands [95] have noted overall levels that were below the 0.5 mg/m 3 recommended by the WHO [96].…”
Section: Childrenmentioning
confidence: 99%
“…Studies conducted in Belgium reported an increased risk of asthma among children with atopy that was associated with early indoor [87][88][89] and outdoor [90] swimming pool attendance. However, studies in other European countries such as Germany [91], Spain [92,93], the UK [94•], and the Netherlands [95], have found no association between swimming pool attendance and respiratory symptoms among children. Studies showing null associations were population-based and had larger sample sizes [91-93, 94•, 95].…”
Section: Childrenmentioning
confidence: 99%
“…2 The harmful effects of chlorine appear to be dependent on concentration and length of exposure, and still require further study. 2,14 A 2009 study by Bemanian et al 15 showed significant improvement in peak expiratory flow rates in asthmatics after swimming, and suggested that indoor swimming is useful for patients with asthma, regardless of the potentially toxic effects of chlorine.…”
Section: Allergy Skin Testingmentioning
confidence: 99%
“…2 On the other hand, increased asthma risk has been associated with asthmatic children swimming in pools, but the evidence is inconsistent and inconclusive. In an attemt to address the issue, Font-Ribera et al 14 studied the effects of swimming and of the hazards associated with pool irritants on Spanish children, and found no increase in asthma risk.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study conducted in Ireland among 121 boys (10) found a significant association between asthma and the number of years attending pools, but not with the frequency of attendance. Studies conducted in Germany (11,12), Italy (13), and Spain (14) did not find an increased risk of asthma among children attending swimming pools. Despite the conflicting results, there is agreement on the complexity of the potential role of swimming in asthma etiology and the important public health implications (1,(15)(16)(17).…”
mentioning
confidence: 99%